(untitled) (Vietnam Journal of Community Medicine, 2023)
Introduction: Adherence to treating out-patients with Diabetes mellitus (DM) is essential to prevent fatal complications. Objectives: The study aimed to assess the treatmeant adherence of type-2 diabetic out-patients in commune 11, Go Vap district, Ho Chi Minh City. Methods: We applied a cross-sectional design to perform direct interviews with 208 type 2 diabetes out-patients (T2DP) in commune 11, Go Vap district, Ho Chi Minh City during March-June, 2022. Findings: 59.1% of T2DP had good knowledge of treatment adherence. 38.9% of T2DP fully adhered to the four recommendations for diabetes treatments. The rate of medication adherence was highest at 89.9%, while the rate of adherence to self-monitoring of blood glucose and follow-up visit was lowest at 40.9%. The adherence rate to dietary was 43.8% and the adherence rate to physical activities was 84.1%. Conclusions: T2DP with fully adhered to the diabetes treatment was low. Commune health centers need to strengthen counseling and communication of health workers to out-patients with lowincome level.